O acento primário do português (Revista de Estudos da Linguagem, 1997)
AbstractThis paper discusses the primary stress rules of Brazilian Portuguese (BP). I argue that i) the primary stress rules are category sensitive –there are two distinct rules in BP: one for non-verb forms which applies at the derivational level (level) and the other for verb forms which applies at the inflectional level (level); ii) the primary stress rules are quantity-insensitive; iii) the extrametricality is determined by morphology and is subject to Peripherality Condition.